Synthesis and characterization of monetite prepared using a sonochemical method in a mixed solvent system of Water/Ethylene Glycol/N, N-Dimethylformamide - Baradaran, Saied; Basirun, Wan Jefrey; Mahmoudian, Mohammad Reza; Abd Shukor, Mohd Hamdi; Alias, Yatimah (Springer Verlag (Germany), 2013)
Bioactive monetite (anhydrous calcium hydrogen phosphate, CaHPO4) has been successfully synthesized using the sonochemical method in the presence of a ternary solvent system of water/ethylene glycol (EG)/N, N-dimethylformamide (DMF). The morphology and chemical composition of the synthesized powders were characterized using field emission scanning electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. The results indicated that with increasing sonication time, the morphology changed slightly from a plate-like one to a combination of plates (flower-like). The formation of flower-like nanosheets requires an optimum time of 40 minutes, and the nanosheets have an average thickness of 210 ± 87 nm. The concentration of DMF clearly influences the morphology and crystal phase of the products. The ideal product was obtained using a water/EG DMF ratio of 1:2. © 2013 The Minerals, Metals & Materials Society and ASM International.